2004
DOI: 10.1051/0004-6361:20040312
|View full text |Cite
|
Sign up to set email alerts
|

A search for late-type supergiants in the inner regions of the Milky Way

Abstract: Abstract. We present the results of a narrow-band infrared imaging survey of a narrow strip (12 wide) around the Galactic equator between 6• and 21• of galactic longitude aimed at detecting field stars with strong CO absorption, mainly late-type giants and supergiants. Our observations include follow-up low resolution spectroscopy (R = 980) of 191 selected candidates in the H and K bands. Most of these objects have photometric and spectroscopic characteristics consistent with their being red giants, and some d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 66 publications
(124 reference statements)
1
25
0
Order By: Relevance
“…The reference continuum was taken on both sides of the feature and interpolated, with the exception of the CO(λ = 2.293 µm) molecular band for which two reference continuum intervals on the shorter wavelength side were used for extrapolation, because there is no suitable continuum near the red edge of the feature. The positions and widths of the passbands used to measure the equivalent widths of the features and their chosen continuum reference points are the same as described in Comerón et al (2004). Uncertainties in the equivalent width measured in this way were estimated by repeating the measurements with different choices of the continuum level.…”
Section: Spectroscopymentioning
confidence: 99%
“…The reference continuum was taken on both sides of the feature and interpolated, with the exception of the CO(λ = 2.293 µm) molecular band for which two reference continuum intervals on the shorter wavelength side were used for extrapolation, because there is no suitable continuum near the red edge of the feature. The positions and widths of the passbands used to measure the equivalent widths of the features and their chosen continuum reference points are the same as described in Comerón et al (2004). Uncertainties in the equivalent width measured in this way were estimated by repeating the measurements with different choices of the continuum level.…”
Section: Spectroscopymentioning
confidence: 99%
“…SiO and OH/IR stars show even redder H−K s colors, which are due to continuum absorption in H-band by water (e.g., Figs. 6 and 7 in Messineo et al 2005;Blum et al 2003;Frogel & Whitford 1987;Comerón et al 2004).…”
Section: H-k S Versus J-h Diagrammentioning
confidence: 99%
“…With a similar technique, Comerón et al (2004) identified 18 RSGs located in the Inner Galaxy. We observed nine of these RSGs, but maser emission was not detected.…”
Section: Trumpler 27mentioning
confidence: 99%
“…With our average rms noise of 0.23 Jy, we report the first unsuccessful searches toward targets in RSGC3, GLIMPSE9, MFD2008 and SGR 1900+14, as well as the isolated RSGs (Blum et al 2003;Comerón et al 2004) discussed in Sect. 6.11 (see Table 3).…”
Section: Clusters Without Sio Maser Detections -Summarymentioning
confidence: 99%